Upaya Peningkatkan Kemampuan Pemecahan Masalah Matematik Melalui Metode Discovery Pada Siswa SMP - Aty Nurdiana; Hesti Noviyana (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
This class action research aims to find out and analyze the improvement of mathematical problem solving abilities of students of class VIII-A of SMP IT Baitul Jannah through the Discovery method.Research problems in the form of low student interest and interest in mathematics so that the effect on the low ability to solve mathematical problems. This research is a Classroom Action Research (CAR) which was carried out in two cycles. The research subjects were students of class VIII-A in the odd semester of Baitul Janah IT Middle School consisting of 12 male students and 19 female students, while the object of the research was the ability to solve mathematical problems. Data collection for each cycleuses test and observation techniques. Data analysis techniques consist of: 1) analysis of the results of observations, 2) analysis of the results of tests of problem solving abilities. To check the degree of data confidence, this study uses triangulation of other research sources, namely the principal, mathematics teacher, and students. Based on the results of data analysis, it can be concluded that there is an increase in students' mathematical problem solving abilities. The increase is from pre-cycle that passed only 9 people or (29.03%) and did not pass 22 people (70.97%) increased in the first cycle to 20 people (64.52%) who passed 11 people (35.48%) did not pass, then in cycle II it became 26 people (83.87%) who graduated and 5 people (16.13%) who did not pass.